High Fischer ratio oligopeptides from Antarctic krill: Ameliorating function and mechanism to alcoholic liver injury through regulating AMPK/Nrf2/IκBα pathways - Xiao-Meng Dong; Shi-Kun Suo; Yu-Mei Wang; Yu-Hui Zeng; Chang-Feng Chi; Bin Wang (Journal of Functional Foods, 2024)
In this study, we devoted attention to the hepatoprotective functions of high Fischer ratio oligopeptides (HFOPs) from Antarctic krill (HFOPs-AK) on alcoholic liver injury of mice. The results indicated that HFOPs-AK significantly improved the pathological state of mice liver and kidney, reduced alanine aminotransferase (ALT) and aspartate transaminase (AST) activities, regulated lipid metabolism, and alleviated the burden on the liver. In addition, HFOPs-AK depicted anti-inflammatory and antioxidant effects by reducing tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) contents and increasing superoxide dismutase (SOD) and catalase (CAT) activities to reduce malondialdehyde (MDA) level. The hepatoprotective mechanism of HFOPs-AK was further revealed by quantitative reverse transcription PCR (RT-qPCR) analysis, and the results proved that HFOPs-AK had the ability to stimulate the adenosine 5‘-monophosphate-activated protein kinase (AMPK)/nuclearrespiratoty factor 2 (Nrf2)/inhibitor of NF-κB (IκBα) signaling pathways, thereby regulating the expression levels of downstream factors. The activation of these signaling pathways is essential for the regulation of lipid metabolism as well as anti-inflammatory and antioxidant functions. This finding offers a novel approach for the development of innovative hepatoprotective agents utilizing HFOPs-AK.